2005
DOI: 10.1002/art.21348
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of quantitative assessment of cartilage morphology by magnetic resonance imaging at 3.0T

Abstract: Objective. Quantitative magnetic resonance imaging (MRI) of articular cartilage represents a powerful tool in osteoarthritis (OA) research, but has so far been confined to a field strength of 1.5T. The aim of this study was to evaluate the precision of quantitative MRI assessments of human cartilage morphology at 3.0T and to correlate the measurements at 3.0T with validated measurements at 1.5T.Methods. MR images of the knee of 15 participants with OA and 15 healthy control subjects were acquired using Siemens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
184
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 189 publications
(198 citation statements)
references
References 14 publications
11
184
1
2
Order By: Relevance
“…A comparison of 3-T and 7-T scans in our study demonstrated significant SNR and CNR increases, in agreement with previous studies [1][2][3]. This study examined the reproducibility of quantitative measurements of cartilage morphology and trabecular bone structure, and indicated comparable reproducibility with those reported at lower field strengths [13,16] for both measurements. A longitudinal patient study is still required to examine the advantages of quantitative musculoskeletal imaging at ultra-high fields.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A comparison of 3-T and 7-T scans in our study demonstrated significant SNR and CNR increases, in agreement with previous studies [1][2][3]. This study examined the reproducibility of quantitative measurements of cartilage morphology and trabecular bone structure, and indicated comparable reproducibility with those reported at lower field strengths [13,16] for both measurements. A longitudinal patient study is still required to examine the advantages of quantitative musculoskeletal imaging at ultra-high fields.…”
Section: Discussionsupporting
confidence: 91%
“…All images were acquired at high resolution (a matrix of 512×512 was used for cartilage measurements, and a matrix of 512×384 was used for trabecular bone structure measurements) to reduce partial-volume effect. The precision errors of repeated measurements of cartilage morphology with similar imaging parameter settings (acquisition matrix=512×512, slice thickness=1 mm) have been evaluated previously at 3 T by Eckstein et al [16]. In their report, the CV ranged between 1.7% and 2.5% for cartilage volume measurements, and between 1.8% and 2.3% for mean cartilage thickness measurements.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We model the MR imaging process for two adjacent sheet structures and used this model to predict the shape of the MR signal intensity profile along the sheet normal direction given in Eq. [9]. The difference between the predicted and actual profiles observed in MR data is minimized by refining model parameters.…”
Section: Proposed Methods Of Thickness Measurement Based On Mr Imagingmentioning
confidence: 99%
“…MRI-based quantitative cartilage thickness measurement techniques have become increasingly important in clinical applications as well as in fundamental research. Although such studies have been performed for approximately a decade, most of them have focus on the knee joint (7)(8)(9)(10)(11). There have been, to date, very few studies on the human hip due to a lack of an appropriate MRI-acquisition protocol that specifically targets the ball and socket hip joint.…”
mentioning
confidence: 99%